2014
DOI: 10.1021/la501711t
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Mediated Adhesion Forces between Borosilicate Glass and Gram-Positive Bacteria

Abstract: It is well-known that a number of surface characteristics affect the extent of adhesion between two adjacent materials. One of such parameters is the surface roughness as surface asperities at the nanoscale level govern the overall adhesive forces. For example, the extent of bacterial adhesion is determined by the surface topography; also, once a bacteria colonizes a surface, proliferation of that species will take place and a biofilm may form, increasing the resistance of bacterial cells to removal. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 64 publications
(142 reference statements)
2
58
2
2
Order By: Relevance
“…According to the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory [34], initial adhesion involves a number of unspecific interactions, namely, van der Waals attractive forces (vdW) and electrostatic repulsive forces. The vdW are the predominant forces while the distances between microorganism and the surface were greater than 50 nm, whereas the combination of vdW and electrostatic interactions governed the bacteria adhesion when at closer distance [35]. Our results showed that nanoscale roughness has positive effect on the S. mutans adhesion forces.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…According to the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory [34], initial adhesion involves a number of unspecific interactions, namely, van der Waals attractive forces (vdW) and electrostatic repulsive forces. The vdW are the predominant forces while the distances between microorganism and the surface were greater than 50 nm, whereas the combination of vdW and electrostatic interactions governed the bacteria adhesion when at closer distance [35]. Our results showed that nanoscale roughness has positive effect on the S. mutans adhesion forces.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, surface roughness is scale-dependent and can be measured in many approaches; therefore, the values of surface roughness parameters may be different at the macroscale compared to the microscale and even at the nanoscale [46]. According to Preedy et al, the correlation between surface roughness and adhesion forces varies as the size of the area is scanned to calculate roughness value [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The first is to understand the interaction between particular bacteria and material surface (32). The second includes food as an intermediate between surface, natural antimicrobials, and bacteria in order to come up with applicable findings for food industry.…”
Section: Discussionmentioning
confidence: 99%
“…A high percentage of adhesion to chloroform (acid and electron acceptor solvent) was observed for most tested strains, which is superior to that for hexane (apolar solvent) and that for ethyl acetate (basic solvent and electron donor). These comparisons demonstrated the basic character and, hence, the electron donor property for most strains (Preedy et al, 2014). CRA method: The slime production of the isolates was evaluated by the Congo Red Agar method (CRA), according to the protocol of Freeman et al (1989).…”
Section: ) Microbial Adhesion To Solvents (Mats)mentioning
confidence: 94%